Existence of nontopological solutions for the generalized Maxwell-Chern-Simons-Higgs model - Song, Kyungwoo (Journal of mathematical analysis and applications, 2022)
In this paper, we study nontopological solutions of the generalized self-dual Maxwell-Chern-Simons-Higgs model in the whole plane. By introducing a scaling parameter ε>0 and regarding the main equations as perturbation of a singular Liouville equation for small ε, we verify the existence of one parametric family of nontopological solutions.